If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + x) = 4(4 + 5) Combine like terms: x + x = 2x x(2x) = 4(4 + 5) Remove parenthesis around (2x) x * 2x = 4(4 + 5) Reorder the terms for easier multiplication: 2x * x = 4(4 + 5) Multiply x * x 2x2 = 4(4 + 5) Combine like terms: 4 + 5 = 9 2x2 = 4(9) Multiply 4 * 9 2x2 = 36 Solving 2x2 = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x2 = 18 Simplifying x2 = 18 Take the square root of each side: x = {-4.242640687, 4.242640687}
| .2x^2+12=3.4 | | 5(x+2)=12-3x | | x=1/2(110) | | ln(x+1)=x-0.8 | | Ln(x^2-25)=ln(-5x-1) | | 24x^2=180 | | Ln(x^2)=ln(-5x-1) | | 5(7n-4)+4=12+7n | | 2x+3z=2+5y | | 9n-8=-458 | | 9a-8=-260 | | 6n-5=271 | | 4p+8=-120 | | 27x^2-4=0 | | 3b+9=150 | | 50*50+140*140=x*x | | 2a=-38 | | 2x^2-12=-5+x | | x=1/2(80+60) | | 38-6n=4(-4n+3)-4 | | 4p=-164 | | x(x+4)+x(2+x)=x(2x)+12 | | -7a=-252 | | -t^2-13t=0 | | -39+6r=3+5(6+3r) | | x=1/2(40) | | -5j=250 | | 2(3x-2)-5(x-1)=1(3) | | -t^2-13=0 | | -8b=184 | | x=1/2(66-54) | | x=1/2(66+54) |